Sosialisasi Pencegahan Stunting Melalui Penerapan Pola Hidup Sehat dan Pemberian Makan Bergizi serta Pencegahan Pernikahan Dini di Desa Rajak Besi Kecamatan Merigi Sakti Kabupaten Bengkulu Tengah - Oktoyoki, Hefri; Ginting, Khairul Ikhwanda; Asriani, Fera; Fernando, ronal; Sari, Novia Perwita; Rimdam, Dian Hasanah; Izzati, Miftahul; Amelia, Amanda; Damaiyana, Tahnia; Rajagukguk, Roy Firmanto; Ansiska, Paisal (Jurnal Pengabdian Arumbai, 2023)
Stunting is a growth disorder in children caused by recurrent infections and chronic malnutrition. It has become a national health issue, with high rates recorded in Indonesia, particularly in Central Bengkulu Regency, specifically in Rajak Besi Village. One of the main causes of stunting is a lack of nutritional intake, which can begin during pregnancy if the mother does not meet nutritional needs. In this village, early marriage is also prevalent. Early marriage, especially among teenagers, has serious consequences. It can halt education, disrupt physical and mental health, and increase the risk of premature births and other health issues. Moreover, early marriage can limit future educational and career opportunities. Efforts to prevent stunting can be carried out through socialization activities and posyandu (integrated health posts) for toddlers and pregnant women. We also conducted socialization to prevent early marriage. Through the program implemented in Rajak Besi Village, we successfully raised public awareness about the importance of providing nutritious food to children and pregnant women, as well as adopting clean and healthy lifestyles. The villagers also began to understand the dangers of early marriage.